A study of maternal dietary intake during pregnancy in Riyadh, Saudi Arabia - Khalid S Almurshed; Ibrahim A Bani; Mohammed A Al-Kanhal; Mohammed A Al-Amri (Wolters Kluwer Medknow Publications, 2007)
Objective : This study was carried out to evaluate the dietary nutrient intake of pregnant women. The relationship between dietary intake and pregnancy outcome was also studied. Method: A total of 114 pregnant women were studied, using systematic random sampling. Results : The percentages of the mean nutrient intake below the recommended dietary allowances (RDA) for pregnant women were as the follows: 51.8%, 93.9%, 82.5% and 98.2% for energy, vitamin B1, calcium and iron, respectively. Moreover, 13.2% of the women experienced some form of pica. Using height and mid-arm circumferences, about 2.8% and 4.4% were seen to be undernourished respectively. Conclusion: Saudi pregnant women need guidance in selecting nutrient dense foods to reduce maternal and outcome health hazards.